Effects of the International Judo Federation Refereeing Rules on the match results and points in the All-Japan Judo Championships - Miyake, K.; Sato, T.; Yokoyama, T. (Archives of Budo, 2016)
Background and Study Aim: The All-Japan Judo Championships (AJJC) is an open-weight tournament to determine the best judoka in Japan. The AJJC has been held under the Kodokan Judo Refereeing Rules (KDK Rules) since 1951. In 2011, the All-Japan Judo Federation introduced the International Judo Federation Refereeing Rules (IJF Rules). In this study, we aimed to clarify the effects of IJF Rules on match results and points in the AJJC.